Communication and Coordination in Zakat Management (Analysis of Synergy Between BAZNAS, LAZ and the Pati Regency Government) - Samsul Mu'arif; Ambarwati Ambarwati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The contestation of authority between zakat management institutions, represented by the government through the National Zakat Agency (BAZNAS) and the community through the Zakat Management Institutions (LAZ), is an unavoidable dynamic in zakat governance in Indonesia. Therefore, concrete steps are needed to build harmony and collaboration to optimize zakat collection in accordance with existing potential. This study uses a descriptive qualitative approach with research objects including BAZNAS, LAZ, and the Pati Regency Government. Data were collected through interviews, observations, and documentation, then analyzed using a descriptive analysis model. The results of the study indicate that a constructive synergy has been formed between zakat management institutions in Pati Regency through two main pillars, namely communication synergy and coordination synergy. This synergy has produced several important achievements: (1) strengthening zakat regulations, including through the issuance of a Regent Regulation on zakat and the initiation of the preparation of a Regional Regulation on zakat; (2) institutional development, such as the establishment of new Zakat Collection Units (UPZ), data collaboration between zakat managers and religious instructors, and the implementation of quarterly coordination between institutions; and (3) synergy of zakat programs, including zakat education and socialization, UPZ development, and zakat distribution not only for the eight ashnaf but also for humanitarian programs such as disaster management. These findings confirm that participatory communication and structured coordination are the keys to the success of zakat institutional synergy at the regional level.